Sensory and consumer science methods used with older adults: A review of current methods and recommendations for the future. (March 2016) - Methven, Lisa; Jiménez-Pranteda, Maria L.; Lawlor, J. Ben
Highlights: Capturing sensory perception and preferences of older adults needs simple methods. Directional forced choice and paired preference tests advised to compare cohorts. Sensory quality for older adults suffering from dementia needs greater attention. Contextual and conceptual factors are key to future research with older adults. Testing with older cohorts needs sufficient study power for reliable conclusions. Abstract: Capturing the sensory perception and preferences of older adults, whether healthy or with particular disease states, poses major methodological challenges for the sensory community. Currently a vastly under researched area, it is at the same time a vital area of research as alterations in sensory perception can affect daily dietary food choices, intake, health and wellbeing. Tailored sensory methods are needed that take into account the challenges of working with such populations including poor access leading to low patient numbers (study power), cognitive abilities, use of medications, clinical treatments and context (hospitals and care homes). The objective of this paper was to review current analytical and affective sensory methodologies used with different cohorts of healthy and frail older adults, with focus on food preference and liking. We particularly drew attention to studies concerning general ageing as well as to those considering age-related diseases that have an emphasis on malnutrition and weight loss. Pubmed and Web of Science databases were searched to 2014 for relevant articles in English. From this search 75 papers concerning sensory acuity, 41 regarding perceived intensity and 73 relating to hedonic measures were reviewed. Simpler testing methods, such as directional forced choice tests and paired preference tests need to be further explored to determine whether they lead to more reliable results and better inter-cohort comparisons. Finally, sensory quality and related quality of life for older adults suffering from dementia must be included and not ignored in our future actions.